THE ROLE OF DIGITAL TECHNOLOGIES IN DEVELOPING STUDENTS’ CREATIVE AND TECHNICAL SKILLS - Raximova Gulsanam Hazrat qizi (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: This article examines the role of digital technologies in the development of students’ creative and technical skills. The study focuses on innovative approaches to integrating digital tools, virtual projects, and interactive multimedia in art and technical drawing lessons. The aim is to enhance students’ independent creative activity, improve technical competence, and stimulate problem-solving and visual thinking skills through the use of modern educational technologies.